2020
DOI: 10.29252/jcc.2.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Production methods of ceramic-reinforced Al-Li matrix composites: A review

Abstract: Recently, the increasing need for good quality, high performance, and low-cost materials has directed research towards composite materials rather than monolithic materials. In the case of metal matrix composites (MMCs), composites based on aluminum matrix have been widely developed for the automobile and aerospace industry as well as structural applications due to having a low cost, high wear resistance, and high strength to weight ratio.Moreover, a facile and economical method for the production of the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…It has been reported that the number of patents in this field showed a 29% growth from 2010 to 2016 while the patent filings began only in 2013 [8]. The reason for significant interest in AIBs is the abundance of Al and its even distribution in the earth [9,10]. Additionally, a very high capacity of up to 8.05 Ah/cm 3 and 2.98 Ah/g can be obtained using multivalent metal ions transmitting internally in the AIBs [11].…”
Section: Abstract a R T I C L E I N F O R M A T I O Nmentioning
confidence: 99%
“…It has been reported that the number of patents in this field showed a 29% growth from 2010 to 2016 while the patent filings began only in 2013 [8]. The reason for significant interest in AIBs is the abundance of Al and its even distribution in the earth [9,10]. Additionally, a very high capacity of up to 8.05 Ah/cm 3 and 2.98 Ah/g can be obtained using multivalent metal ions transmitting internally in the AIBs [11].…”
Section: Abstract a R T I C L E I N F O R M A T I O Nmentioning
confidence: 99%
“…In the past 15 years, a considerable section of research activities has been allocated to self-healing materials [11][12][13]. The aim of using self-healing materials is to restore the mechanical and physical integrity and properties rapidly after being damaged.…”
Section: Tbc Modificationmentioning
confidence: 99%
“…Therefore, in Fig. 2, due to the large diameter of the induction loop compared to the time constant of high frequencies, the polarization resistance of aluminum in 3.5 wt.% sodium chloride solution is estimated to be about 200 Ω.cm 2 . Fig.…”
Section: Eis Testmentioning
confidence: 99%
“…Aluminum and its alloys are of particular importance in the industry due to their light weight, excellent chemical resistance, especially in neutral environments, and high strength to weight ratio [1][2][3]. They are mainly used in the aerospace, automotive, oil and gas, and drilling industries.…”
Section: Introductionmentioning
confidence: 99%